Ice‐Wedge Evidence of Holocene Winter Warming in the Canadian Arctic. Issue 12 (13th June 2020) - Holland, Kira M.; Porter, Trevor J.; Froese, Duane G.; Kokelj, Steven V.; Buchanan, Casey A.
Abstract: Arctic summer temperatures mostly cooled over the last 7 kyr, owing to decreasing summer insolation. However, knowledge of the winter season is limited in the Arctic paleoclimate literature. Here we develop a composite record of δ 18 O from ice wedges—a winter precipitation archive—to reconstruct changes in winter climate in the northwestern Canadian Arctic since 7.4 kyr b2k. Our record shows a long‐term δ 18 O enrichment (+(0.14 ± 0.10)‰ kyr −1 ), suggesting winter temperatures increased since the mid‐Holocene, a finding that is corroborated by reconstructions from the Siberian Arctic. Winter warming over the last 7 kyr is consistent with increasing winter insolation and greenhouse gas forcing. This study provides some of the first insights on the sensitivity of winter temperatures in the Canadian Arctic to past, and potentially future, climate forcings, and contributes to a more seasonally holistic understanding of the Arctic system. Plain Language Summary: The history of climate change during the last 11, 700 years, a period known as the Holocene Epoch, has been traditionally studied using natural climate proxies such as tree rings or pollen in the sedimentary record. Such records allow us to better understand past climate variability in response to changing greenhouse gas concentrations, solar radiation, and other boundary conditions. However, most traditional climate proxies are biological and sensitive mainly to growing‐season conditions, whereas changes in cold‐season conditions are not well described in the literature. This is especially true in the Arctic where recent climate warming has been most pronounced in the winter season, but few cold‐season‐specific proxy records are available. In this study, we develop a 7, 400‐year record of the δ 18 O isotope composition of relict ice wedges in the northwestern Canadian Arctic, a proxy type that is specifically sensitive to cold‐season conditions. We observe a long‐term increase in ice‐wedge δ 18 O over the past 7, 400 years, indicating warming winter temperatures since the mid‐Holocene. This warming corresponds to increasing winter solar radiation and greenhouse gas concentrations and is in agreement with recent reports from ice wedges in the Siberian Arctic. Key Points: Ice‐wedge δ 18 O reveals an enrichment trend over the last 7.4 kyr The enrichment reflects a long‐term winter warming trend, coinciding with increasing winter insolation and greenhouse gas forcing This record provides key insights on winter Holocene climate not previously described by other records in this region